MiR-33a-5p Targets RAP2A to Mediate the Sensitivity of Gastric Cancer Cells to 5-FU. (22nd August 2022) - Ti, Gang; Guo, Zongliang; Li, Lili; Lv, Yongqiang; Yang, Bin; Wang, Jian; Guo, Rui; Chen, Yunqing; Meng, Debin; Li, Feng
Abstract : Objective . The objective of this study is to explore the effects of microRNA-33a-5p (miR-33a-5p)-ras-related protein Rap-2a (RAP2A) on biological functions of gastric cancer (GC) and to find the potential functional mechanism. Methods . We measured the miR-33a-5p expression in 30 GC tissues and cellular level and 30 adjacent normal tissues as control. Besides, the expression of miR-33a-5p was checked at cell level as well. To screen the possible targets of miR-33a-5p, prediction software was used and gene RAP2A attracted our attention. Through a series of experiments including real-time polymerase chain reaction (qRT-PCR), luciferase assay, and western blotting (WB), we verified RAP2A as a potential target of miR-33a-5p. The impacts of miR-33a-5p and RAP2A on biological functions of GC cell lines (BGC-823 and MGC-803) were analyzed by subsequent experiments. Cell invasion was tested by invasion assays. Cell proliferation was measured by cell counting kit-8 (CCK-8) assay. Cell clone was measured by clone formation assays. Finally, the expression of RAP2A protein was analyzed by WB assay. Results . We found miR-33a-5p was expressed lowly in GC tissues and cells. Overexpression of miR-33a-5p in BGC-823 and MGC-803 cells greatly inhibited the cell invasion and colony number. Furthermore, compared to sh-control (shControl), RAP2A knockdown (sh-RAP2A/shRAP2A) raised the sensitivity of GC cells to 5-FU significantly, characterized as reducing cell apoptosis. Conclusions . The expression of miR-33a-5p was lower in GC cell lines and tissues obviously, indicating that miR-33a-5p served as the antitumor gene in GC. The expression of RAP2A regulated negatively the sensitivity of GC cells to 5-FU. According to our in vitro experiments, miR-33a-5p/RAP2A was likely to become a new therapeutic target for GC.